Development of Simple Fractions Mathematics E-Module to Improve Understanding of Grade 3 Students in Online Learning at Elementary Schools in Sidoarjo Regency: Pengembangan E-Modul Matematika Pecahan Sederhana untuk Meningkatkan Pemahaman Siswa Kelas 3 dalam Pembelajaran Daring di Sekolah Dasar Kabupaten Sidoarjo - Mayasari, Widya; Istikomah, Istikomah (Indonesian Journal of Education Methods Development, 2022)
During the COVID-19 pandemic for the 2020-2021 school year, Rangkah Kidul Elementary School carried out online learning. The online learning of simple fractions for grade 3 conducted at SDN Rangkah Kidul is less than optimal because it is more dominant in assignments and is teacher-centered. So that the ability of students to understand the material of simple fractions is lacking. For that we need interesting teaching materials that can be read and studied anywhere and anytime and can improve student understanding. This research aims to create and develop teaching material products in the form of e-modules. Therefore, this study examines the steps of e-module development, the feasibility of e-modules, and the effectiveness of the simple fractions mathematics e-module in improving the understanding of 3rd graders at SDN Rangkah Kidul. This research is a development research with ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Collecting data using questionnaires, tests, and documentation. The analysis technique uses a value comparison formula, pair sanple t test, and linear regression with the help of the SPSS 16 program. The results of the study explain the steps of e-module development which consist of analyzing needs and problems, compiling and planning learning objectives, developing products through feasibility tests, implementing products with field trials, and evaluate product use. Then the results of the feasibility of the e-module by material experts 87.14% and media experts 92.31% and field trials to 24 students of 94.91% meaning that the e-module is very feasible. Furthermore, there is the effect of using e-modules on increasing students' understanding with an increase in class average from 78.50 to 89.08 and the magnitude of the effect is 66.4%. In conclusion, the development of the simple fractions math e-module is feasible and effective to improve the understanding of grade 3 students in online learning at SDN Rangkah Kidul.